Study of the Physical and Morphological Properties of Ceramic Insulator - Hussein, I. F. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
In this investigation insulator ceramic body was prepared by using iraqi local materials, these are kaolin, silica sand glass, feldspar with weight percentage (45%,25%, 30%)respectively.  After the end of treating drying and milling of raw material mixing with different concentrations of sodium silicate(1%,0.7%,0.5%,0.2%,0.1%) while zinc oxide was added at fixed weight percentage.  A disc samples was prepared after compaction and then fired by sintering temperatures (1250, 1350)oC respectively.A surface morphology was studied by using optical microscope and measurements of apparent density and porosity was under taken to the sintered samples by using Archimedes method.The study showed that the microscopic images for samples surface showed that grains start in convergence with other and grain size increasing with firing temperature and the best result of apperant density and porosity at 0.5%  concentration of sodium silicate .